solve for x

20(2x - 8) = 440

13 answers

To solve for x, let's first simplify the equation:

20(2x - 8) = 440

First, we will distribute 20 to the terms inside the parentheses:

40x - 160 = 440

Next, let's isolate the variable x by adding 160 to both sides of the equation:

40x = 440 + 160

40x = 600

Finally, we will divide both sides of the equation by 40:

x = 600/40

x = 15

Therefore, the solution for x is 15.
Solve for x
0.72 = 0.4 (x + 1.4)
To solve for x, we will first distribute 0.4 to the terms inside the parentheses:

0.72 = 0.4x + 0.4(1.4)

Next, we will simplify the expression:

0.72 = 0.4x + 0.56

To isolate the variable x, we will subtract 0.56 from both sides of the equation:

0.72 - 0.56 = 0.4x + 0.56 - 0.56

0.16 = 0.4x

Finally, we will divide both sides of the equation by 0.4:

0.16/0.4 = (0.4x)/0.4

0.4 = x

Therefore, the solution for x is 0.4.
Solve for x
2(1.5x - 7) = 6
To solve for x, let's start by distributing 2 to the terms inside the parentheses:

2(1.5x - 7) = 6

2 * 1.5x - 2 * 7 = 6

3x - 14 = 6

Next, we want to isolate the variable x. To do that, we'll add 14 to both sides of the equation:

3x - 14 + 14 = 6 + 14

3x = 20

Finally, divide both sides of the equation by 3 to solve for x:

3x/3 = 20/3

x = 20/3

Therefore, the solution for x is x = 20/3.
what is 20/3 in decimal form?
To convert 20/3 to decimal form, we divide 20 by 3:

20 รท 3 = 6.6667 (rounded to four decimal places)

Therefore, 20/3 in decimal form is approximately 6.6667.
Solve for x
5x - 2x + 4 = -5
To solve for x, let's start by combining like terms on the left side of the equation:

5x - 2x + 4 = -5

(5x - 2x) + 4 = -5

3x + 4 = -5

Next, we will isolate the variable x by subtracting 4 from both sides of the equation:

3x + 4 - 4 = -5 - 4

3x = -9

Finally, divide both sides of the equation by 3 to solve for x:

3x/3 = -9/3

x = -3

Therefore, the solution for x is x = -3.
Solve for x
9x + 9x - 21 = 33
To solve for x, let's start by combining like terms on the left side of the equation:

9x + 9x - 21 = 33

(9x + 9x) - 21 = 33

18x - 21 = 33

Next, we will isolate the variable x by adding 21 to both sides of the equation:

18x - 21 + 21 = 33 + 21

18x = 54

Finally, divide both sides of the equation by 18 to solve for x:

18x/18 = 54/18

x = 3

Therefore, the solution for x is x = 3.
Solve for x
14x - 3x + 11 = -22
To solve for x, we'll start by combining like terms on the left side of the equation:

14x - 3x + 11 = -22

(14x - 3x) + 11 = -22

11x + 11 = -22

Next, we will isolate the variable x by subtracting 11 from both sides of the equation:

11x + 11 - 11 = -22 - 11

11x = -33

Finally, divide both sides of the equation by 11 to solve for x:

11x/11 = -33/11

x = -3

Therefore, the solution for x is x = -3.